Detection of Immunoglobulin G and/or IgM antibodies specific for Lassa virus among HIV patients in the Northwestern region of Cameroon - Lem Edith Abongwa; Kelvin Njefi; Ntonifor Helen Ngum; Teboh Rogeson; Muhammad Ahmed; Oluremi Israel Ajayi; Gerades Dely Djoufack; Philomena Eromon; Chinedu Ugwu; Onikepe Folarin; Christian Happi (Virology Journal)
Abstract Background Persons with HIV are prone to other infections. Lassa virus (LASV)coinfection with HIV is a public health concern. Viral hemorrhagic fever caused by LASV has been endemic in parts of West Africa. Clinical diagnosis has been a major challenge for effective management and control because the majority of patients are asymptomatic. As such, rapid diagnosis is desirable for prompt therapeutic intervention and the implementation of control measures. The high prevalence of LASV recorded in Nigeria, a neighboring country, places Cameroon at risk. However, the detection of LASV infection among HIV patients, which we investigated in this study, has not been carried out in Cameroon. Methods Plasma samples were obtained between December 2021 and April 2022 from 330 HIV-positive patients who provided consent. They were tested for LASV IgG and/or IgM antibodies specific for LASV nucleoprotein and/or prefusion envelope glycoproteins via the ReLASV® Pan-Lassa Combo NP/Prefusion GP IgG/IgM ELISA Test Kit according to the manufacturer’s instructions. The data were analysed via SPSS and GraphPad. Results Analysis of these samples revealed that IgG and both IgG and IgM antibodies were detected in 2.4% (8/330) and 1.8% (6/330) of the samples, respectively. Our data revealed that both IgG and IgM antibodies do not depend (p > 0.05) on age, sex, or duration of antiretroviral therapy (ART), although the prevalence was high in individuals < 25 years of age, males, and those who had taken ART for < 5 years. The mean ODs of both IgG (0.6 0vs 0.03) and IgM (0.88 vs. 0.04) were significantly greater (p < 0.05) between LAVS-positive and LAVS-negative patients. Conclusions The finding of this study shows co-infection of HIV and Lassa Virus. The presence of LASV-specific antibodies suggests exposure to LASV. These findings have direct implications for understanding the transmission risk, mitigation, and prevention and control of LASVs in Cameroon. Our results indicate the urgent need to extend LASV surveillance if there is recurrent LASV infection in any country.